Trends and patterns of analgesic prescribing in Malaysian public hospitals from 2010 to 2016 : Tramadol predominately used - Zin, Che Suraya; Mohamed Nazar, Nor Ilyani; Ab Rahman, Norny Syafinaz; Alias, Nor Elina; Ahmad, Wan Rohaidah; Rani, Nurul Sahida; Cardosa, Mary Suma; Ng, Kim Swan; Ye, Felicia Loh (Dove Press Ltd, 2018)
Purpose: To examine the trends of analgesic prescribing at public tertiary hospital outpatient settings and explore the patterns of their utilization in NSAIDs, tramadol and opioid patients.